A Facile One-Step Synthesis of Fe2O3 Nanoparticles/Reduced Graphene Oxide for Enhanced Hydrazine Sensing. Issue 2 (14th January 2017) - Yang, Ziyin; Zheng, Xiaohui; Zheng, Jianbin
Abstract : Fe2 O3 nanoparticles/reduced graphene oxide (Fe2 O3 /rGO) nanocomposites were synthesized for enhanced electrochemical sensing of N2 H4 . Fe2 O3 /rGO nanocomposites were synthesized through a green and facile one-step hydrothermal approach by using L-lysine as both reductant and hydrolysis-controlling agent. Then, the nanocomposites were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction spectroscopy (XRD), energy-dispersive X-ray spectrum (EDS), fourier transform infrared spectroscopy (FTIR) and electrochemical techniques. SEM and TEM observations revealed that large numbers of Fe2 O3 nanoparticles with spherical morphologies were distributed on the surface of rGO sheets, which made the sensor based on Fe2 O3 /rGO exhibited an excellent performance toward N2 H4 detection with a wide linear range of 0.8 μM to 1.27 mM, a high sensitivity of 525.3 μA mM −1 cm −2 and a low detection limit of 0.09 μM (S/N = 3). Therefore, the facile approach and excellent experimental results indicated that Fe2 O3 /rGO nanocomposites can be applied as a promising type of sensing material for electrochemical detection of N2 H4 .